STUDY OF PHYSICO AND MECHANICAL PROPERTIES OF SOLUTIONS FOR CONCRETING UNDER THE WATER - Klochko, B. H.; Krasniuk, A. V.; Momot, V. O. (Science and Transport Progress, 2006)
In the article are brought studies a physicist-mechanical characteristics an dissolves for concreting under water. On results of studies movable and toughness features is designed optimum compositions for filling under pressure at the concrete transport erecting repair under water.